Empowering Santri in Addressing Environmental Preservation Issues through Essay Writing Based on Pesantren’s Local Wisdom in Temanggung - Zaidatul Arifah; Luluk Ifadah; Afidatun Rofi'ah; Dea Puji Saputri (FOUNDAE (Foundation of Advanced Education), 2025)
Islamic boarding schools (Pondok Pesantren), as religious-based educational institutions, have great potential to address environmental conservation issues. Temanggung is an area with a large santri community that has the potential to drive environmental conservation. However, challenges such as low awareness among santri and limited environmental development facilities are major obstacles. This community service activity aimed to empower students (santri) through essay writing based on the local wisdom of their pesantren. The main goal of the activity was to increase the awareness, writing skills, and active involvement of the students in sustainable environmental conservation. This research involved 20 students from 10 Islamic boarding schools in Temanggung Regency, as well as pesantren administrators, local government officials, community organisations, and a nature lovers' community. The Asset-Based Community Development (ABCD) model was used in this study to analyze the potential of the students, develop strategies, and evaluate the results of the community service. The research findings showed that the students were a potential asset for the pesantren in formulating solutions for environmental problems that were based on local wisdom. This essay writing training program produced three main strategies for empowering santri: essay writing training, essay publication, and empowerment through contextual experiences based on environmental conservation. The implementation of these three strategies proved effective in increasing the students' understanding, awareness, and participation. Through the environmental awareness-based essay writing activities, the students were hoped to become the leading pioneers of environmental awareness, especially within the pesantren environment, in a sustainable way.